Detailed assessment and risk factor analysis of corticosteroid-induced psychiatric disorders in pediatric, adolescent, and young adult patients undergoing induction or consolidation therapy for hematologic malignancy. (July 2020) - Staub, Yukiko; Suga, Yukio; Ikawa, Yasuhiro; Tsubouchi, Kiyotaka; Hashimoto, Mikie; Kawagishi, Atsufumi; Shimada, Tsutomu; Sai, Yoshimichi; Nishimura, Katsuji; Matsushita, Ryo
Background: Corticosteroid-induced psychiatric disorders (CIPDs) represent an adverse effect that can cause severe emotional and behavioral problems. The aim of the present study was to assess the incidence and risk factors of CIPDs. Methods: A retrospective analysis of 92 pediatric and young adult patients with hematologic malignancies was conducted. Results: The incidence of CIPDs in patients receiving a treatment regimen with prednisolone or dexamethasone was 64.9% and 77.5%, respectively, both of which were significantly higher than that in patients not receiving corticosteroids. Independent risk factors and adjusted odds ratios (95% confidence intervals) related to severe CIPD were 2.15 (1.11–4.18) for dexamethasone (using prednisolone as the reference) and 0.81 (0.75–0.87) for age, suggesting that the odds increase with decreasing age. Frequently observed symptoms, respectively in terms of behavioral and emotional problems were defiance, crying, psychomotor excitement, dysphoria, irritability, and depression. To our knowledge, this is the first report to mention the risk factors and characteristics for clinical symptoms of CIPDs during the developmental process. Conclusions: Healthcare professionals should predict and prepare for psychiatric adverse events prior to chemotherapy in the clinical settings, especially in patients in younger age and receiving a treatment regimen with dexamethasone.